A variable frequency angle-based repetitive control for torque ripple reduction in PMSMs - Tang, Mi; Gaeta, Alberto; Formentini, Andrea; Zanchetta, Pericle (2016)
This paper presents a novel method for torque ripple reduction in PMSM drives at variable speed, using a combination of angle-based repetitive control and deadbeat current control. Based on the internal model principle, repetitive control is capable to reduce periodic torque ripple by generating a compensating action that consequently need to be synchronized with the original ripple. The time to angle, angle to time conversions for repetitive control, which improve both the stability and the performance when the sampling frequency is not integer multiple of the speed, are presented. A transient detection strategy is also developed to allow a stable torque ripple reduction even during speed and load changes.